Democracy and Modern State: Siyasah Shar’iyyah Analysis - Syatar, Abdul (Jurnal Al Tasyri'iyyah, 2021)
This article aims to reveal the intersection of the relevance of democracy in the modern state system and the system of government in Islam. This research uses a socio-cultural approach. The results show that democracy has two essential aspects, namely as a system and form of the state, and as universal values that are fought for the sake of human dignity. In the first aspect, as a system and form of state, democracy cannot meet the concept of Islam because it does not speak of a particular system and form of a state. Islam is more of a religion and a social rule of life, not talking about a system, let alone the form of a state. In the second aspect, human values must be fought. Democracy can be in line with Islamic teachings. It covers the value of egalitarianism (al-musāwah), freedom (al-huriyah) and pluralism (ta` adudiyah), does not contradict Islamic principles, even long before Islam has spoken about and fought for these values. It does not mean that democracy is entirely following the spirit and breadth of Islam. Islam also contains other principles that democracy does not carry. The principles in question are the principles of syūrā (deliberation). From this understanding of democracy, what the Islamic democratic system wants to aim at is the implementation of Islamic teachings as a whole and consequently to create a benefit as aspired by siyāsah syar'iyah.Keywords: Democracy; Islamic Politics; Modern State; Siyasah Shar’iyyah